2009
DOI: 10.3109/00365520903483650
|View full text |Cite
|
Sign up to set email alerts
|

Faecal calprotectin and lactoferrin are reliable surrogate markers of endoscopic response during Crohn's disease treatment

Abstract: The faecal neutrophil-derived proteins calprotectin and lactoferrin are reliable surrogate markers of mucosal improvement. Endoscopic responders achieved normalization of faecal biomarkers, whereas in the majority of endoscopic non-responders these markers remained abnormal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 33 publications
2
88
1
1
Order By: Relevance
“…It is simple and inexpensive to measure using ELISA, and shows a strong direct correlation between FC values and CD activity as measured by clinical, endoscopic and even histological indices (5,16). It is highly accurate for establishing endoscopic activity and is considered to be the most accurate indirect parameter for mucosal healing (17,18). It is also useful for identifying patients in deep remission who have fewer probabilities of relapsing in the short term (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is simple and inexpensive to measure using ELISA, and shows a strong direct correlation between FC values and CD activity as measured by clinical, endoscopic and even histological indices (5,16). It is highly accurate for establishing endoscopic activity and is considered to be the most accurate indirect parameter for mucosal healing (17,18). It is also useful for identifying patients in deep remission who have fewer probabilities of relapsing in the short term (19).…”
Section: Introductionmentioning
confidence: 99%
“…Both studies observed considerable heterogeneity between the various tests due to a lack of diagnostic methodology standardization as there are so few studies evaluating endoscopic activity. The two studies proposed different cut-offs for FC: 50 µg/g (5,21), 100 µg/g (17,22,23), 250 µg/g (24,25) and 274 µg/g (26), with no agreement on the optimum cut-off level.…”
Section: Introductionmentioning
confidence: 99%
“…Another important feature is the differential level of FC according to the site of IBD where it is found to be significantly higher in active colonic rather than ileal CD [30]; and in left-sided/distal UC than ulcerative pancolitis [31]. Finally, FC could be used as a marker for treatment assessment [32] as it decreases considerably after anti-TNF therapy, and it correlates with CD endoscopic index of severity (CDEIS) [33] as well as endoscopic mucosal healing [34]. Koulaouzidis, et al suggested that FC can direct the use of special costly investigations as capsule endoscopy which can be declined if FC level is less than 100 μg/g [35].…”
Section: Markers In Current Usementioning
confidence: 99%
“…Table 2 reports the sensitivity and specificity of lactoferrin, calprotectin and of CRP in discriminating between active and inactive IBDs [47][48][49][50][51][52][53][54]. High levels of calprotectin/lactoferrin are also predictive of relapse for both UC and CD [55,56].…”
Section: Ibds -Laboratory Diagnosis Fecal Markersmentioning
confidence: 99%
“…Calprotectin, a 36.5 kDa hetero-trimer, consisting of one S100A8 light chain and two S100A9 heavy chains belonging to the S100 calcium binding proteins family, is present in the cytoplasm of granulocytes and accounts for about 60% of soluble proteins; it is secreted extracellularly from stimulated neutrophils and monocytes or released by cell disruption or death [44]. Both lactoferrin and calprotectin have antimicrobial properties: histidine-based zinc-binding sequences (His-X-X-X-His motif) are involved in the antimicrobial activity of calprotectin, while the amino-terminal domain (lactoferricin) liberated by pepsin Røseth et al [47] CD and UC 77%/100% Solem et al [48] CD 54%/75% D'Incà et al [49] CD 77%/80% 81%/80% D'Incà et al [49] UC 75%/60% 78%/70% Sipponen et al [50] CD 77%/100% 87%/100% Schoepfer et al [51] UC 86%-93%/71%-88% Schoepfer et al [52] CD 89%/58% 68%/58% Sipponen et al [53] CD 80%/67% 80%/89% Lobatòn et al [54] UC 74%/90% 84%/38%…”
Section: Lactoferrin and Calprotectin: Biochemical Properties Pre-anmentioning
confidence: 99%